Nrf2 Activation Is Involved in Cyclic Mechanical Stress-Stimulated Osteogenic Differentiation in Periodontal Ligament Stem Cells via PI3K/Akt Signaling and HO1-SOD2 Interaction - Xi, Xun; Li, Zixuan; Liu, Hong; Chen, Shuai; Liu, Dongxu (Frontiers in Cell and Developmental Biology, 2022)
Nuclear factor erythroid-2-related factor-2 (Nrf2), the major transcriptional regulator in antioxidant response and cellular defense, had the vital effect on regulating osteogenic differentiation. Our previous study revealed that up-regulated Nrf2 expression was involved in cyclic mechanical stress-stimulated osteogenic differentiation in the human periodontal ligament stem cells (PDLSCs). However, the mechanisms of Nrf2 underlying this process remain unclear. The goal of the study was to explore the mechanisms of Nrf2 in PDLSCs during cyclic mechanical stress-stimulated osteogenic differentiation via the tandem mass tag (TMT)-based liquid chromatography tandem-mass spectrometry (LC-MS/MS) analysis. And we applied tert-Butylhydroquinone (t-BHQ), the Nrf2 activator, to the orthodontic rats and detected the changes of the osteogenesis marker expressions by immunohistochemistry (IHC) staining. Our results showed that Nrf2 activation in PDLSCs was involved in cyclic mechanical stress-stimulated osteogenic differentiation via phosphoinositide 3 kinase (PI3K)/protein kinase B (Akt) pathway. The protein-protein interaction between Akt and Nrf2 was observed. And the protein-protein interaction between heme oxygenase-1 (HO-1) and superoxide dismutase 2 (SOD2), the downstream antioxidants of Nrf2, was involved during cyclic mechanical stress. T-BHQ enhanced the expressions of osteogenesis markers in orthodontic rats. Nrf2 might possess the potential to be a feasible molecular target in orthodontics.